1,1,2,2-Tetrakis(diisopropylamino)diphosphane - Grubba, Rafał (International Union of Crystallography, 2009)
In the title compound, C(24)H(56)N(4)P(2), the distance between the P atoms [2.2988 (8) and 2.3013 (13) Å in the major and minor occupancy components, respectively] is one of the longest reported for uncoordinated diphosphanes. The whole molecule is disordered over two positions with site-occupation factors of 0.6447 (8) and 0.3553 (8). The structure adopts the synperiplanar conformation in the solid state [N—P—P—N torsion angle = 14.7 (5)°].